Meningkatkan Pemahaman Interaksi Sosial dengan Metode Permainan pada Anak Panti Asuhan: Improving Understanding of Social Interaction with Game Methods for Children in Orphanages - Purwaningtyastuti, Purwaningtyastuti; Savitri, Anna Dian; Pratiwi, Margaretha Maria Shinta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The community service carried out is entitled Increasing Understanding of Social Interaction with Game Methods for Children in Orphanages. The problem that arises is that orphanage children who come from different family backgrounds tend to often cause the orphanage children's social relationships to be less harmonious, even though they live together in the orphanage. This service aims to provide an understanding of how good social interaction is to improve relationships. between one orphanage child and another orphanage child so that harmony is created in the family of the orphanage child. The method that will be used for this service is a pre-post test, games that support social interaction, and feedback or evaluation of the games provided. The result of this activity is that after gaining information and insight into social interaction through games and sharing sessions as well as feedback from each game, the orphanage children finally understand and understand how good social interaction is. Besides that, the orphanage children can capture the meaning and benefits of the games that have been played. This activity concludes that the children from the orphanage responded quite well, and looked happy and enthusiastic so they got an idea and knowledge about what good social interaction is like, which also includes good communication, collaboration with friends, sharing, and learning from each other togetherness.